Designing Optimal Whistleblowing Mechanisms: A Qualitative Literature Review on Bounty Size, Strategic Thresholds, and Regulatory Effectiveness - Ahembang; Selvi Agustina (LPPM STIE Kasih Bangsa, 2026)
This qualitative literature review explores how bounty size, strategic thresholds, and regulatory effectiveness shape the design and outcomes of whistleblowing mechanisms. By synthesizing empirical and theoretical insights from leading accounting and finance journals, the study identifies three interrelated findings: first, that larger bounty rewards increase reporting volume but may reduce signal quality; second, that insiders’ reporting thresholds are influenced by retaliation risk, compensation incentives, and perceived enforcement credibility; and third, that regulatory backlogs and discretion can distort the intended deterrent effect of whistleblowing policies. The review highlights the need for a holistic design approach that integrates incentive alignment with institutional capacity and protection mechanisms. Limitations in jurisdictional generalizability, demographic heterogeneity, and the evolving role of digital reporting platforms are also discussed. Recommendations for future research include examining whistleblowing in non-U.S. contexts, integrating organizational culture, and assessing the role of emerging technologies